THE RUSSIAN LANGUAGE: SYSTEMIC CRISIS? - Chuzhakin, A.P.; Alexeeva, I.S.; Romanchik, R.E.; Karu, K.; Kondakov, B.V.; Chugaeva, T.N.; Nazmutdinova, S.S.; Shpak, N.E. (Perm Federal Research Centre Journal, 2015)
On the 4th of June 2014 Perm Scientific Centre, Ural Branch of Russian Academy of Sciences held a round table discussion devoted to "The Crisis of the Russian language and culture - is there light at the end of the tunnel?". The issues of the current state of the Russian language were discussed by the participants of the I International Scientific Conference "The Russian language in the bilingual translation discourse" hosted by Perm National Research Polytechnic University (June 2-4, 2014) in Perm. The Conference was organised within the framework of support for the Russian language and education by Ministry of Education and Science of RF and Pushkin State Russian Language Institute.